2012
DOI: 10.5001/omj.2012.112
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Serum Testosterone, Free Androgen Index, and Calculated Free Testosterone in Women with Suspected Hyperandrogenism

Abstract: The diagnosis of hyperandrogenism was most obvious when using CFT or FAI than testosterone alone. It is thus recommended to include these calculated parameters (CFT and/or FAI) in the routine investigation and assessment of women with disorders related to clinical or biochemical hyperandrogenism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 16 publications
0
50
0
Order By: Relevance
“…In our present cohort, the 99th percentile for T concentration is calculated at 3.08 nmol/L. It is close to the 2.78 nmol/L threshold proposed as one of the criteria for the diagnosis of PCOS (29) and the 3.0 nmol/L cutoff proposed by others (30) to detect hyperandrogenism. This finding should clearly help to refine more evidence-based fair policies and recommendations concerning hyperandrogenism in female athletes.…”
Section: Discussionmentioning
confidence: 97%
“…In our present cohort, the 99th percentile for T concentration is calculated at 3.08 nmol/L. It is close to the 2.78 nmol/L threshold proposed as one of the criteria for the diagnosis of PCOS (29) and the 3.0 nmol/L cutoff proposed by others (30) to detect hyperandrogenism. This finding should clearly help to refine more evidence-based fair policies and recommendations concerning hyperandrogenism in female athletes.…”
Section: Discussionmentioning
confidence: 97%
“…Instead around half is tightly bound to sex hormone binding globulin, and the other half is weakly bound to albumin. Only a small percentage is unbound, under 3% in females, and less than 0.7% in males [4]. Since only the free testosterone is able to bind to tissue receptors to exert its effects, it is believed that free testosterone is the best marker of a person's androgen status.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies performed in Turkey (14) and Oman (15), have concluded that total testosterone and AFI are effective in diagnosing hyperandrogenism, although they reported the AFI being the superior test.…”
Section: Discussionmentioning
confidence: 93%